The depressor response to intracerebroventricular hypotonic saline is sensitive to TRPV4 antagonist RN1734 - Feetham, Claire H.; Nunn, Nicolas; Barrett-Jolley, Richard (Frontiers in Pharmacology, 2015)
Several reports have shown that the periventricular region of the brain, including the paraventricular nucleus (PVN), is critical to sensing and responding to changes in plasma osmolality. Further studies also implicate the transient receptor potential ion channel, type V4 (TRPV4) channel in this homeostatic behaviour. In previous work we have shown that TRPV4 ion channels couple to calcium-activated potassium channels in the PVN to decrease action potential firing frequency in response to hypotonicity. In the present study we investigated whether, similarly, intracerebroventricular (ICV) application of hypotonic solutions modulated cardiovascular parameters, and if so whether this was sensitive to a TRPV4 channel inhibitor. We found that ICV injection of 270mOsmol artificial cerebrospinal fluid (ACSF) decreased mean blood pressure, but not heart rate, compared to naïve mice or mice injected with 300mOsmol ACSF. This effect was abolished by treatment with the TRPV4 inhibitor RN1734. These data suggest that periventricular targets within the brain are capable of generating depressor action in response to TRPV4 ion channel activation. Potentially, in the future, the TRPV4 channel, or the TRPV4–KCa coupling mechanism, may serve as a therapeutic target for treatment of cardiovascular disease.